Quality of life and the duration of treatment with vitamin K antagonists in patients with deep venous thrombosis - Locadia, Mirjam; Sprangers, Mirjam A.G.; de Haes, Hanneke C.J.M.; Büller, Harry R.; Prins, Martin H. (Thrombosis and Haemostasis, 2003)
In clinical practice, decisions on the duration of treatment with vitamin K antagonists are usually based on the presence of persistent risk factors, the risk of bleeding and centre policy. Little is known about the influence of patients’ experienced quality of life. The objectives of this study were: 1) to explore the course of quality of life in patients with venous thrombosis treated for 3 months versus patients treated for 6 months with vitamin K antagonists; 2) to investigate the factors that were associated with the duration of treatment with vitamin K antagonists. The study sample comprised patients participating in a multi-centre clinical trial. Quality of life was assessed at study entry, after 10-14 days,3 and 6 months in 360 patients. Overall, no dif-ferences in quality of life were found between the 2 patient groups. An interaction effect between group and time was found for physical functioning. Regression analyses indicated that the presence of one or more permanent risk factors, duration of hospitalisation, mobility prior to deep-vein thrombosis and study centre were associated with the duration of treatment with vitamin K antagonists. Interestingly, quality of life was not associated with treatment duration. Since study centre was the most important factor associated with treatment duration, local policy appears to have a great influence on decisions regarding the duration of treatment with vitamin K antagonists.Part of this manuscript has been included in a poster presentation at the International Society for Quality of Life Research in Amsterdam, The Netherlands, November 8, 2001.
Keywords: Vitamin K antagonists; quality of life; duration of treatment